Label-free immunosensor for morphine based on the electrochemiluminescence of luminol on indium–tin oxide coated glass functionalized with gold nanoparticles. Issue 11 (7th June 2015) - Ya, Yang; Xiaoshu, Wang; Qing, Da; Lin, Jiang; Yifeng, Tu
<x xml:space="preserve">Abstract</x> We report here the development of an immunosensor for morphine based on electrochemiluminescence using luminol as the probe.